Sustainable Urban Farming: Budidaya Ikan Hias dan Ikan Rawa di Pekarangan Rumah - Fajar Basuki (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Basuki F. 2021. Sustainable urban farming: ornamental and swamp fish cultivation in the home yard. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 11-18. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Indonesia has a lot of potential land resource for fresh water cultivation including swamp resource, the purpose of this paper is to talk about ornamental and swamp fish cultivation in the house yard that easily to do, to be expected it will increasing household revenue. Result based on experience and literature review, if in the location has enough fresh water and the pH water is 7 for cultivation, it is possible to cultivate the Goldfish (Carasiuas auratus Linnaeus, 1758), starting from preparation for resulting broodstock, and then is spawning using fish pond or aquarium, maintaining the larva until it becomes harvest seeds according to the size, and the last is transporting it safely. But, if in the location has enough fresh water but the pH water under 7, so it is still possible to cultivate rasbora fish (Rasbora einthovenii Bleeker,1851), starting from preparation for resulting broodstock, and then is spawning using fish pond or aquarium, maintaining the larva until it becomes harvest seeds according to the size, and the last is transporting it safely.